Similar biological activity in skin prick test for Oralair® (8200 BAU) and Grazax® (6200 BAU) reinforces effective SLIT dosing level. Issue 12 (12th September 2016) - Larenas Linnemann, D. E. S.; Singh, J.; Rosario, N.; Esch, R.; Matta, J. J.; Maspero, J.; Michels, A.; Mösges, R.
Abstract: In Europe, allergen extracts are standardized based on skin prick wheal size in 20–30 allergic subjects. To understand the biological activity of clinically effective Sublingual immunotherapy, we used this method to determine the biological activity of solution and tablet Timothy grass pollen (TIM) extracts, compared to an FDA‐approved extract (Reference) of 10 000 BAU/ml. Blinded, quadruplicate skin prick tests with concentrate and three serial half‐log dilutions allowed the construction of a semilogarithmic regression line per extract. Bioequivalent allergy units (BAU) values were obtained from the comparison with reference. Extracts and dilutions showed a neat linear dose response (all: R 2 > 0.98) in 33 rhinitis patients. Relative potencies: Staloral ® 12 000 BAU/ml, Soluprick ® 10 300 BAU/ml, Oralair ® 8200 BAU, and Grazax ® 6200 BAU. Even though all extract concentrates differed in wheal size ( P = 0.01–0.001), Grazax ® producing a 25% smaller wheal size than Oralair ®, and the biological activity of these clinically effective TIM tablets led in the same range (6200–8200 BAU; 0.92–1.23 cm 2 ). SLIT dose‐finding studies for other pollens might start with allergen extracts producing 1.1 cm 2 wheal surface.